FESTIVAL PENGGING FAIR BOYOLALI DALAM PERSPEKTIF MODERASI BERAGAMA ALA NAHDLATUL ULAMA DAN MUHAMMADIYAH - Zulfa Wahda Anindita; Purwanto Purwanto (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The cultural diversity in Indonesia makes this country rich in various cultural activities and celebrations held in various regions of Indonesia. So the focus in this article is on the role of the two largest community organizations in Indonesia, namely Nahdlatul Ulama (NU) and Muhammadiyah, in participating in the Pengging Fair festival activities, which are identical and steeped in the culture of the Pengging kingdom and its historical heritage, so that they can display a moderate Islamic image. The research method used was a descriptive-qualitative approach. The research subject is the chairman of the 2018 Pengging Fair Committee (Muhammad Rifqi). The data collection techniques used were non-participatory observation, documentation studies, and interviews. The conclusions of this article are: first, the multicultural approach promoted by Nahdlatul Ulama (Islam Nusantara), which is synonymous with preserving local traditions; and second, the concept of religious moderation, which is in accordance with Muhammadiyah's Progressive Islamic thinking, which is identical with the concept of modernity and openness in facing the flow of globalization. Both of them managed to unite at the Pengging Fair Festival and prove that Islam is the religion of Rahmatan lil 'alamin.